The Role of Educational Innovation in E-Learning: A Literature Study - Rosyidah Muhammad; Dhieka Avrilia Lantana; Kumba Digdowiseiso (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Educational innovation in e-learning has become an important subject of study in contemporary educational transformation. The background to this research reflects a shift in the learning paradigm from conventional methods to technology-based learning models. The aim of this study is to examine the role of educational innovation in e-learning, with a focus on its impact on educational accessibility, personalization of learning, and learning effectiveness. The research method used is a literature review, by analyzing a number of studies and related sources that have been carried out by education experts. The results reveal that educational innovations in e-learning have opened up access to education to more people, overcoming geographic and social barriers. Personalization of learning through technology has improved student learning outcomes and motivation. E-learning also allows for more accurate evaluation of student progress and provides a more interactive learning experience